Vitamin A content in Peranggi (Capsicum annuum L. var. chinensis), a local chili pepper from West Kalimantan - Daningsih, Entin; Safitri, Dwi; Hartini, Sari Sugi; Marlina, Reni (Jurnal Biologi Tropis, 2025)
Peranggi chili (Capsicum annuum L. var. chinensis) is a local chili variety with high spiciness and a distinctive aroma from West Kalimantan; however, its quality, including vitamin A content, are not known yet. This study aimed to assess the quality, including the vitamin A content, of Peranggi chili. The experimental design was a Completely Randomized Block Design (RCBD), with sampling time as blocks and different markets as treatments, each with three replications. The measurements included weight, length, diameter fruit, peduncle length, peduncle weight, color, namely (L, a, b) and lastly vitamin A content. Data were analyzed using SAS with the ANOVA model for RCBD, followed by the Least Significant Difference (LSD) test if the treatments were significant. Multiple regression analysis was applied to identify the quality variables that determine vitamin A content. The weight, length, and diameter fruit of Peranggi chili was smaller in shape and size compared to other Capsicum annuum varieties. The size pranggi chili varietdD. Vitamin A content also varies and was more influenced by the maturity level of the chili (a and L values). The resulting data can serve as a basis for grading the quality of Peranggi chili, including its vitamin A content.